In-Situ Experimental Assessment and Numerical Analysis of the Loading Capacity of Traditional Wooden Floors. Issue 9 (20th October 2020) - Negrão, João; Vicente, Romeu; Ferreira, Tiago Miguel; Martins, Alberto; Raimundo, Ana
ABSTRACT: A procedure for the load test and subsequent data processing for the structural assessment of traditional wooden floors is proposed. The load test consists of suspending a point load from one individual timber beam while controlling its deflection and that of adjacent beams. The test setup is simple and requires no special conditions or materials that may not be available on site by inspection time, such as lifting equipment, containers or water supply. This scheme has the major advantage of easily accounting for the local heterogeneity of the floor, resulting of the variability of the individual timber beams, associated to growth characteristics, sawing and service defects or biologic attack. Based on the geometric data collected on site and estimated mechanical properties, a numeric finite element model is defined and the deflection evaluated at the same monitored points of the load test. An optimization process using an entropy-based method is finally carried out in order to change the design variables (elastic moduli and stiffness of the load-share systems) so that the analytic values match the experimentally recorded deflections. Finally, a local (simplified) model of the deck was used in the present study to perform an analysis-optimization.